2021
DOI: 10.1007/s10143-021-01488-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of combined use of intraoperative MRI and awake microsurgical resection on patients with gliomas: a systematic review and meta-analysis

Abstract: Microsurgical resection of primary brain tumors located within or near eloquent areas is challenging. Primary aim is to preserve neurological function, while maximizing the extent of resection (EOR), to optimize long-term neurooncological outcomes and quality of life. Here, we review the combined integration of awake craniotomy and intraoperative MRI (IoMRI) for primary brain tumors, due to their multiple challenges. A systematic review of the literature was performed, in accordance with the Prisma guidelines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In addition, tractography has poor reproducibility, with results depending on numerous factors [ 5 ]. All considered, it is perhaps unsurprising that there is hesitancy within the neurosurgical community to adopt intraoperative tractography [ 6 ], even as interest in intraoperative MRI [ 7 , 8 ] and tractography for surgical planning and navigation [ 9 , 10 ] grows. Currently intraoperative streamline tractography is mostly limited to the often outdated tools available in commercial navigation software [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tractography has poor reproducibility, with results depending on numerous factors [ 5 ]. All considered, it is perhaps unsurprising that there is hesitancy within the neurosurgical community to adopt intraoperative tractography [ 6 ], even as interest in intraoperative MRI [ 7 , 8 ] and tractography for surgical planning and navigation [ 9 , 10 ] grows. Currently intraoperative streamline tractography is mostly limited to the often outdated tools available in commercial navigation software [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scherer et al (7) and Ghinda et al (15) reported two large iMRI case series. Tuleeasca et al conducted a meta-analysis using the latest iMRI data (26). In the studies using iUS, Shetty et al (23) and Munkvold et al (24) recruited large, unselected cohorts of gliomas at neurological centers with extensive iUS experience.…”
Section: The Surgical Results and Comparison With The Literature Datamentioning
confidence: 99%
“…The reduction of iMRI scans was due to fewer patients requiring further resections. Further resection was recorded in 17.5% of patients, compared to 46% in the previous iMRI case series (13)(14)(15)26). One iMRI scan session needs about 30-70 minutes when using the high field iMRI system (13)(14)(15)39).…”
Section: Improved Surgical Efficiencymentioning
confidence: 90%
See 1 more Smart Citation
“…The authors did not give specific data about the number of iMRI scans. While In the reported iMRI case series, around 46% (26.1-52.2%) (14)(15)(16)23) patients needed multiple iMRI scans. Reducing the number of iMRI scans also might effectively decrease the complexity of the iMRi-assisted surgeries.…”
mentioning
confidence: 96%